Climate variability indices for ecological and crop models in R: the climatrends package - Sousa, Kauê de; Etten, Jacob van; Neby, Magne; Solberg, Svein Øivind (Open Journal, 2023)
Abiotic factors play an important role in most ecological and crop systems that depend on certain levels of temperature, light and precipitation to initiate important physiological events (Schulze et al., 2019). Understanding how these factors drive the physiological processes is a key approach to provide recommendations for adaptation and biodiversity conservation in applied ecology studies. The package climatrends aims to provide the methods in R (R Core Team, 2020) to compute precipitation and temperature indices that serve as input for climate and crop models (Kehel et al., 2016; van Etten et al., 2019), trends in climate change (Aguilar et al., 2005; de Sousa et al., 2018) and applied ecology (Liu & El-Kassaby, 2018; Prentice et al., 1992).